Inclusive Study of Religions and World Views in Schools: Signposts from the Council of Europe - Jackson, Robert (Social Inclusion, 2016)
This article outlines some issues in incorporating the study of religions, together with non-religious world views, into the curricula of publicly funded schools in Western democratic states. Attention is given to examples from work on this topic conducted within the Council of Europe since 2002, with a particular focus on Signposts: Policy and Practice for Teaching about Religions and Nonreligious World Views in Intercultural Education, a text published by the Council of Europe in 2014. Signposts is designed to assist policy makers and practitioners in interpreting and applying ideas from the 2008 Recommendation from the Committee of Ministers (the Foreign Ministers of the 47 member states) dealing with education about religions and non-religious convictions. Various issues raised by the Signposts document are considered. Towards the end of the article, recent UK and Council of Europe policies which emphasise the study of religions and beliefs as a means to counter extremism, and which have appeared since the publication of Signposts, are summarised and discussed critically. Attention is drawn to the dangers of certain policies, and also to the plurality of aims which studies of religions and non-religious world views need to have in providing a balanced educational programme.